Pertumbuhan dan Hasil Tanaman Bawang Daun (Allium fistulosum L.) Pada Jarak Tanam Dan Pemotongan Bibit Yang Berbeda - Fera, Aprillia Rosita; Sumartono, GH; Tini, Etik Wukir (Politeknik Negeri Lampung., 2019)
Due to the rising market demands of spring onion (Allium fistulosum L.) it is necessary to response them with the best technical plantation. This research is meant to know: (1) the effective plant spacing, (2) the effective seedlings tuber cutting, and (3) to decide the interaction between plant spacing and the seedlings tuber cutting spring onion. The research was done on April 2018 until June 2018 at Dusun Gewok, Desa Karanggintung, Kecamatan Sumbang, Kabupaten Banyumas. The design of the research is a Randomized Complete Block Design (RCBD) with two factors. The first factor is the plant spacing which consist of 3 levels, (15 x 20) cm, (20 x 20) cm, and (25 x 20) cm. The second factor is seedling tuber cutting which consist 3 levels, without cutting, cutting ½ part, and cutting 2/3 part. The data analyzed using F test, then continued using Duncan?s Multiple Range Test (DMRT) on level 5%. The result showed that the most effective to reach the higher level and the best yield is the plant spacing 15 cm x 20 cm with 1.729 g, the seedlings tuber cutting ½ part raise the hight of the plant 56,12 cm, and there is no best combination between the spacing of the seedlings to cut the seedlings to increase the growth and yield of the spring onion.